Increasing the Brand Awareness of Heyboba Drinks to Its Target Market Through Instagram - Noviyanti Chintia Dewi; Jusuf Imam Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2022)
Heyboba is an SME that sells boba drinks that experienced a decline of about 50% in its sales. The writer conducted a survey using Google Forms on customers and non-customers. The results show that the problem that caused the decline in sales is the lack of brand awareness from the target market, such as many people do not know Heyboba and its USP. It happened because Heyboba was less active in informing its USP on social media. Therefore, the writer decided to create USPs content as a solution where the content highlights the USPs of Heyboba like the low product price, delicious and different taste of boba, having delivery services, and having a point card on Instagram according to the branding theory by Mira Shabrina (2015). By displaying the USPs of Heyboba, the writer believes that it can increase the brand awareness of the target market and increase Heyboba's sales.